Interrelationships among Locus of Control and Years in Management and Unemployment: Differences by Gender - Eileen Trzcinski; Elke Holst (Deutsches Institut für Wirtschaftsforschung (DIW), 2010)
This paper focuses on gender differences in the role played by locus of control within a model that predicts outcomes for men and women at two opposite poles of the labour market: high level managerial / leadership positions and unemployment. Based on data from the German Socio-Economic Panel, we investigated the extent to which gender differences occur in the processes by which highly positive and negative labour market outcomes are determined and in the processes underlying the development of one particular aspect of personality, that is, locus of control. Overall gender differences were more pronounced in the results for years in managerial/ leadership positions than for locus of control. Negative labour market states were also marked by gender differences, but not to the same degree observed for positive states.
Keywords: J1; J24; J60; M51; 330; Geschlecht; Persönlichkeitspsychologie; Führungskräfte; Weibliche Führungskräfte; Arbeitslosigkeit; Frauenarbeitslosigkeit; Deutschland